THE CONCEPT OF MARKET BALANCE IN THE DEMAND AND SUPPLY FUNCTIONS IN ECONOMIC MATHEMATICS - Dian Ponco Pratiwi; Dedek Kustiawati; Rivia Zulfa Ananda; Annisa Rizka Wardhani (Quantitative Economics Journal, 2021)
A market is a place where a group of sellers and buyers have real or potential interactions, and set the price of a product or a set of products. In other words, the market can be referred to as a place where the price of an item is set. In simple terms, the market is a meeting place for sellers and buyers to carry out buying and selling transactions. An interactive system in the market, of coursexx there is a concept of demand and supply for an item or service. In economic mathematics, the concepts of demand and supply are interrelated and have interrelationships. In economic mathematics, the market environment is a buying and selling transaction. In buying and selling transactions, everyone makes supply and demand which results in market balance